Acute interstitial nephritis in the military hospital of Morocco: Clinical features and renal outcomes - Yassir Zajjari; Dina Montasser; Aya Sobhi; Taoufiq Aatif; Mounia Azizi; Ahmed Alayoud; Driss El Kabbaj (Saudi Journal of Kidney Diseases and Transplantation, 2019)
Acute interstitial nephritis (AIN) is a common cause of acute kidney injury, possibly with increasing incidence over recent years; therefore, epidemiological studies provide important information for clinical practice and investigations. The aim of this retrospective study was to describe the clinical features and outcome of patients with biopsy-proven AIN in a region of Morocco. All native renal biopsies (January 2008 to December 2017) on adults were reviewed, but only AIN cases were analyzed. Of the 407 renal biopsies performed in this period, 30 patients were included. The mean age of the patients was 47.1 ± 16.7 years; female gender was preponderant (60%). At the time of biopsy, the serum creatinine level was 33.9 ± 11.8 mg/L. The classic triad of fever, skin rash, and eosinophilia occurred in three (10%) patients. The common causes of AIN were drugs in 13 (43.3%) patients followed by autoimmune diseases in 11 (33.3%) patients. At six months postbiopsy, 26.7%, 33.3%, and 40% had partial, complete, and no recovery, respectively. In this study, a good outcome was associated with autoimmune diseases (P = 0.02) and with a higher intensity of interstitial edema (P = 0.01). However, a presence of a granuloma (P = 0.04), a higher percentage of interstitial fibrosis (P <0.01), and glomerulo-sclerosis (P <0.01) were associated with no recovery and steroids seem to have no effect in the recovery (P = 0.14).This information provides a contribution toward understanding the epidemiology of acute renal failure in Africa, with implications in planning future prospective studies.